Limb girdle muscular dystrophy 23 caused by compound heterozygous mutations of LAMA2 gene - Xu, Yuqing; Zhu, Linyan; Qian, Yeqing; Dong, Minyue (Frontiers in Pediatrics, 2023)
Introduction Mutations of LAMA2 gene are associated with congenital muscular dystrophy (CMD). The LAMA2-related CMD mainly consists of two diseases, merosin deficient congenital muscular dystrophies type 1A (MDC1A) and limb girdle muscular dystrophy 23 (LGMD23). LGMD23 is characterized by slowly progressive proximal muscle weakness, which primarily affects the lower limbs and results in gait difficulties. Additional clinical features include increased serum creatine kinase, abnormal electromyography with or without white matter abnormalities on brain imaging. Methods Clinical data were collected from a Chinese Han family. Whole-exome sequencing, Sanger sequencing, RT-PCR and TA clone sequencing were performed on the family members. Results Compound heterozygous mutations of LAMA2: c.1693C > T (p. Q565*) (maternally inherited) and c.9212-6T > G (paternally inherited) were identified and confirmed in the proband. The mutation c.1693C > T (p. Q565*) was classified as pathogenic according to American College of Medical Genetics and Genomics (ACMG) guidelines. By performing RT-PCR and TA clone sequencing, an insertion of 40-bp intronic sequence (intron 64) was found in the transcripts of the proband and her father, which resulted in a frameshift and premature truncation codon of the LAMA2. In particular, the variant truncated the LamG domain of the LAMA2. Therefore, the c.9212-6T>G was classified as likely pathogenic according to American College of Medical Genetics and Genomics (ACMG) guidelines. Discussion Our findings described two novel mutations in a girl with LGMDR23, which contributes to the genetic counseling of the family and expands the clinical and molecular spectrums of the rare disease.